Experimental Investigation of the Effect of Solar Collector’s Inclination Angle on the Generation of Thermosiphonic Flow - Panayiotou, Gregoris; Kalogirou, Soteris A.; Florides, Georgios A.; Roditis, George; Katsellis, Nasos; Constantinou, Andreas; Kyriakou, Paraskevas; Vasiades, Yiannis; Parisis, Thomas; Michaelides, Alexandros; Nielsen, Jan Erik (My University, 2014)
Cyprus is currently the leading country in the world with respect to the application of solar water heaters for domestic applications, with more than 93 % of the houses equipped with such a system. The great majority of these solar water heaters are of the thermosiphonic type. Currently, the knowledge about the parameters affecting the ‘thermosiphonic phenomenon’ is rather poor while on an international level (International Organization for Standardization, ISO, and Comité Européen de Normalisation CEN committees) there is no standard available to test thermosiphon solar collectors. The deeper understanding of the ‘thermosiphonic phenomenon’ and the identification of the key parameters affecting it is the main aim of a research project currently in process in Cyprus. In this chapter, the experimental results of the research project are presented. Specifically, a special test rig was set up and equipped with all the sensors necessary to measure all the parameters that are most likely to affect the ‘thermosiphonic phenomenon’. All tests were conducted according to ISO 9459-2:1995(E). The system was able to operate in various weather and operating conditions and could accommodate the change of inclination of the collector. During the experimental procedure, three different inclination angles of the solar collector were tested in order to evaluate their effect on the generation of thermosiphonic flow. The thermal performance of the collector was calculated both in thermosiphonic operation and also according to EN12975-2:2006 in order to determine the thermal performance at a flow and operation conditions specified by the standard. Finally, a series of correlations were attempted using the experimental results for the thermosiphonic operation of the collector which are the following: (i) the temperature difference of the water at the outlet and the inlet of the collector (ΔT) with solar global radiation, (ii) the water mass flow with the solar global radiation and (iii) the water mass flow with the temperature difference of the water at the outlet and the inlet of the collector. The results of the data analysis showed that the examined parameters were well correlated and also the optimum inclination angle in terms of the highest thermosiphonic flow generation was that of 45°.
Keywords: Thermosiphonic phenomenon; Solar water heaters; Cyprus